Eprinomectin antiparasitic affects survival, reproduction and behavior of Folsomia candida biomarker, and its toxicity depends on the type of soil - Serafini S.* (2019)
© 2019 Elsevier B.V.The objective of this study was to evaluate the toxicity of the antiparasitic agent eprinomectin in two subtropical soils, using ecotoxicological lethality, reproduction and avoidance behavior tests with springtails (Folsomia candida). Eprinomectin concentrations were 0 (control), 0.5, 1, 2, 4, 8, 12, 16 and 20 mg kg−1 of dry soil combined with either Entisol or Oxisol soils. Statistically significant toxic effects of eprinomectin on springtails were observed in both soils. Eprinomectin was lethal starting at 8 mg kg-1 of dry soil in Entisol, and 20 mg kg−1 of dry soil in Oxisol, with effects less than 50% at lethal concentrations. Reductions in the reproduction rate of the springtails were also observed starting at 8 mg kg−1 of dry soil in Entisol, and 0.5 mg kg−1 of dry soil in Oxisol. ECrepr50 value calculated for Entisol was 4.38 ± 0.62 mg kg-1 of dry soil; for Oxisol the ECrepr50 was above the highest tested concentration. For avoidance behavior, the effect occurred from 0.5 mg kg-1 of dry soil for both soils. In Entisol, all concentrations caused avoidance of more than 95%, and in Oxisol the ECavoi50 value was 1.33 ± 0.83 mg kg-1 of dry soil. We conclude that eprinomectin affected survival, reproduction and caused avoidance behavior of F. candida in both soils. The toxic effects were greater as the concentration in the soils increased. The effects in Oxisol were less intense than those in Entisol with respect to the affected springtails. This discrepancy may be attributed to the different physicochemical characteristics of the soils that determine the retention capacity for eprinomectin; in particular, there are greater contents of clay, organic matter and cation exchange capacity in Oxisol.